The Effects of Co-Culture of Embryonic Stem Cells with Neural Stem Cells on Differentiation - Ye Rim Kim; Si Won Jang; Jae Ho Han; Ga Rim Na; Hoon Jang; Hyun Woo Choi (Current Issues in Molecular Biology, 2022)
Researching the technology for in vitro differentiation of embryonic stem cells (ESCs) into neural lineages is very important in developmental biology, regenerative medicine, and cell therapy. Thus, studies on in vitro differentiation of ESCs into neural lineages by co-culture are expected to improve our understanding of this process. A co-culture system has long been used to study interactions between cell populations, improve culture efficiency, and establish synthetic interactions between populations. In this study, we investigated the effect of a co-culture of ESCs with neural stem cells (NSCs) in two-dimensional (2D) or three-dimensional (3D) culture conditions. Furthermore, we examined the effect of an NSC-derived conditioned medium (CM) on ESC differentiation. OG2-ESCs lost the specific morphology of colonies and Oct4-GFP when co-cultured with NSC. Additionally, real-time PCR analysis showed that ESCs co-cultured with NSCs expressed higher levels of ectoderm markers Pax6 and Sox1 under both co-culture conditions. However, the differentiation efficiency of CM was lower than that of the non-conditioned medium. Collectively, our results show that co-culture with NSCs promotes the differentiation of ESCs into the ectoderm.